Health Services Utilization and Customer Satisfaction in the Inter-Local Health Zones in Lanao del Norte Region X - F. Resurreccion, Pamela; c. Fajardo, Stephen; E. Coyoca, Gloria Sheila; W. Bokingo, Julita (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Despite the health reforms instituted by thn Philippine government so improve the delivery of health cure services, the stigma of poor health conditions continues to prevail in the country. This study aims to determine the levels of awareness, utilization of and satisfaction on the health care services available in the District Hospitals (DHs), Rural Health Units (RHUs), and Barangay Health Stations (BHSs) of the various Inter Local Heath Zones ALHZs) in Lanao del Norte. In order to meet these goals, descriptive statistics was employed. Through unaded and aided recall, the study found that respondents are more aware of immunization, laboratory, out-patient, and prenatal services; more proportion of respondents seek illness-related care in district hospitals and preventive care from Barangay Health Stations. respondents were satisfied with the quality of health care in District Hospitals, Rural Heaith Units, and Barangay Health Stations. The respondents also identified that spiritual care in the most imparlent sorvioa astruta while noutness of emplayens is the lanst important servica alribar. Accordingby aome reoommendatione are forvarded: do provide trainings an interpersonal communication, corvico emellenc, project proposal writing, information and education campaigas on preventive care services. These recommendations are glured towards future research directions while at the same Lime addrassing the allocation and distribution of medicines lo tho local health caro facilities in Inter Local Health Zones with particular attention to Barangay Health Stations.